Analyzing Influence of Mix Design Constituents on Compressive Strength, Setting Times, and Workability of Geopolymer Mortar and Paste - Damilola Oyejobi; Mohammed Jameel; Adekunle Adewuyi; Samuel Aina; Siva Avudaiappan; Nelson Maureira-Carsalade (Advances in Civil Engineering)
Geopolymer concrete and mortar have evolved over the years as potential alternatives for reducing the greenhouse gases associated with cement production. This current research was aimed at investigating the optimum dosage and concentration of sodium hydroxide required to leach out silica and alumina oxides in the fly ash for geopolymerization to take place. Blackish grey fly ash from Morupule, Botswana, was synthesized by varying sodium hydroxide (NaOH) of 98% purity between 8 M and 14 M, respectively. The ratio influence of sodium hydroxide to fly ash in dissolving the oxides was carried out at the values of 0.55, 0.62, and 0.75. The results showed that the workability of the geopolymer mortar and paste decreased with the increase in the ratio of fly ash to alkaline activator. The highest workability was achieved at a ratio of 0.75 : 1. The compressive strength, setting time, and workability of geopolymer mortar and paste can be controlled by adjusting the ratio of fly ash to alkaline activator. A ratio of 1.5 : 1 was found to be the most suitable for achieving high compressive strength, while a ratio of 0.75 : 1 was found to be the most suitable for achieving high workability. Furthermore, the workability values were in the range of 105 to 143 mm, while the ranges of initial and final setting times were found to be between 280–350 and 950–1170 minutes, respectively. This study is significant because no previous study has carried out geopolmerization of the Morupule fly ash as a result of its unique characteristics. These findings have important implications for the development of sustainable construction materials. The main finding was that for optimum reaction to take place, and NaOH/fly ash ratio should be kept at 0.55 and molarity of 12 to avoid leaching of other oxides that might weaken the strength.